The Special Legal Order and the Renewed Strategies and Normative Framework of Security and Defence Policies in Hungary - Móré, Sándor; Szilvásy, György Péter (Academic and Applied Research in Military and Public Management Science, 2024)
Recent years have brought challenges of arguably unprecedented number and scale to the global security and defence policy environment of states and international organisations. It is probably enough to mention, among many other crises, the Russian–Ukrainian conflict, the Covid–19 pandemic, the internationalisation of terrorism, the increased migratory pressure on Europe, as well as climate change or the emerging threats in cyberspace. Both international and national legislators are looking for new types of responses to these novel forms of challenges. Accordingly, in recent years, Hungary has started to build a new legal environment for defence and security. In our study, we will first consider the strategic framework of this new legal framework, followed by a description of the amended special legal order rules of the Fundamental Law and the new laws that implement the renewed organisation of the comprehensive defence and security system. The future of the subject at hand is unfortunately bleak; yet it may be somewhat clearer if the responses to international conflicts and other threats are underpinned by active preparation.